Perception of Postgraduate Students on Ethical Public Relations Practice in Ebonyi State University, Abakaliki, Nigeria - Orji-Egwu, Agatha Obiageri; Nworie, Happiness Chinenye (Advances in Social Sciences Research Journal, 2023)
In every organization, Public Relations serve as a vital anchor that keeps its reputation and external relationships afloat. It is a shield that minimizes risk and damage upon progress, initiating robust growth and evolution. The rationale for this study is that every successful public relations activity is guided by certain moral principles and is geared towards ensuring that the communication needs of all key stakeholders are addressed. These obviously include the postgraduate students of Ebonyi State University who constitute a critical component of the university publics. Besides, in building the reputation of an organization, it has to start with the internal publics. It is against this backdrop that it becomes imperative to assess the practice of ethical public relations as perceived by postgraduate students among the university staff at Ebonyi State University. The objectives were to determine whether Ebonyi State University postgraduate students perceive the level of communication flow between the students and staff as highly commendable; ascertain the level of goodwill elicited from postgraduate students and as well determine the major challenges that confront the postgraduate students. The study was anchored on a two-way symmetrical model. A mixed research method was adopted for this study and data were gathered using a questionnaire and in-depth interviews with staff of the public relations unit of Ebonyi State University. The population of the study consists of 990 postgraduate students in the 9 faculties of the university between 2018 to 2022 academic sessions. The population includes 88 PGDs, 540 Masters, and 362 PhDs. A sample of 285 respondents was chosen for the study based on the Australian sample size online calculator. The findings of the study revealed that poor communication and inadequate feedback mechanism pose serious challenges to the ethical practice of public relations at Ebonyi State University. It was therefore recommended that in order to build and enhance healthy relationships between the university and its postgraduate students, it is vital to find innovative ways to communicate with the postgraduate students to keep them not only engaged but informed.